2020
DOI: 10.3892/mmr.2020.11206
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatic analysis of the potential molecular mechanism of PAK7 expression in glioblastoma

Abstract: The present study aimed to determine the potential molecular mechanisms underlying p21 (rac1)-activated kinase 7 (PaK7) expression in glioblastoma (GBM) and evaluate candidate prognosis biomarkers for GBM. Gene expression data from patients with GBM, including 144 tumor samples and 5 normal brain samples, were downloaded. long non-coding rnas (lncrnas) and messenger rnas (mrnas) were explored via re-annotation. The differentially expressed genes (deGs), including differentially expressed mrnas and differential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Xue et al analyzed signaling pathways in GBM data compared to normal brain tissue, and found overlapping signaling pathways from gene and miRNA expression, which included ion transport, positive regulation of macromolecule metabolic process, cell cycle and axon guidance as the main enriched signaling pathways [ 36 ]. Similarly, differentially expressed genes were also found, by Wang et al, that are involved in enriched signaling pathways, such as axon guidance [ 37 ].…”
Section: Discussionmentioning
confidence: 95%
“…Xue et al analyzed signaling pathways in GBM data compared to normal brain tissue, and found overlapping signaling pathways from gene and miRNA expression, which included ion transport, positive regulation of macromolecule metabolic process, cell cycle and axon guidance as the main enriched signaling pathways [ 36 ]. Similarly, differentially expressed genes were also found, by Wang et al, that are involved in enriched signaling pathways, such as axon guidance [ 37 ].…”
Section: Discussionmentioning
confidence: 95%
“…Research by Huang et al showed that PNMA5 plays an oncogene role in NSCLC and can promote the occurrence of bone metastasis 50 . Through genome-wide differential expression gene screening, Wang et al observed that PNMA5 was significantly differentially expressed in glioblastoma cancer tissues, and it was closely related to the prognosis of glioblastoma 51 . The prognosis of glioblastoma patients with high expression of PNMA5 was poor 51 .…”
Section: Discussionmentioning
confidence: 99%
“…Through genome-wide differential expression gene screening, Wang et al observed that PNMA5 was significantly differentially expressed in glioblastoma cancer tissues, and it was closely related to the prognosis of glioblastoma 51 . The prognosis of glioblastoma patients with high expression of PNMA5 was poor 51 . Based on the TCGA colon cancer cohort, Zhou et al found that PNMA5 is significantly differentially expressed in colon cancer, and high expression of PNMA5 is associated with poor prognosis of colon cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence has shown that p21-activated kinase (PAK7) regulates carcinogenesis in a variety of malignancies ( Gu et al, 2013 ; Han et al, 2014 ; Quan et al, 2020 ; Wang et al, 2020 ). Suppression of PAK7 increased radio-sensitivity in hepatocellular carcinoma (HCC) ( Gu and Kong, 2021 ).…”
Section: Introductionmentioning
confidence: 99%